Family physicians and cancer care. Palliative care patients' perspectives. - Norman, A. (2001)
OBJECTIVE: To explore factors that affect the integrity of palliative cancer patients' relationships with family physicians and to ascertain their perceptions of their FPs' roles in their care. DESIGN: Qualitative study using grounded-theory methods, taped semistructured interviews, and chart reviews. SETTING: Two palliative care hospital wards in Winnipeg, Man. PARTICIPANTS: A purposeful sample of 11 men and 14 women. METHOD: Qualitative content analysis of interview transcripts. MAIN FINDINGS: Cancer care is organized in a sequential, parallel, or shared manner between FPs and cancer specialists, with sequential care a common outcome if patients' relationships with their FPs wane. Cancer patients can lose contact with FPs because of patient or physician relocation, distrust over delays in diagnosis, failure to perceive a need for FPs, poor communication between FPs and specialists, and a lack of FP involvement in the hospital. People with cancer value FPs for being accessible through prompt appointments and telephone contact; for providing emotional and family support; and for referral, triage, and general medical care. CONCLUSION: Family physicians can enhance care of cancer patients. Contact with FPs can be maintained by ensuring good communication between specialists and FPs, defining a clear role for FPs, addressing concerns about delays in diagnosis, and referring patients back to FPs, particularly after hospitalization.